(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Long Song (2010) is a modern Caribbean novel that explores the theme of slavery, written by Andrea Levy. The story explores the era of slavery during the early 19th century in Jamaica, focusing on the life of a slave girl named July who resides at Amity, a sugarcane estate. Set against the historical backdrop of a renowned Jamaican slave uprising, the Baptist War, which occurred in 1831, and the subsequent abolition of slavery in 1833, this novel provides a detailed account of the lives of the enslaved individuals on Jamaican plantations both prior to and during their emancipation. The work extensively examines the ethnic and cultural backgrounds of the persons residing on the plantations, where the British class structure predominates, with a strong focus on the issue of identity. Therefore, this article will examine how the British social order significantly impacts the identity of slaves in the Caribbean. Additionally, it will examine the diminishing potential and significance of the British class system in Jamaica following the Baptist War.